Acid mucopolysaccharides in human liver tissue. II: Acid mucopolysaccharides in the human liver with or without cirrhotic changes - NAKAMURA, Nobuto; KOJIMA, Junnosuke; KANATANI, Masako; OHMORI, Kiyohiko (Kanzo, 1975)
Total amount and constituents of acid mucopolysaccharides (AMPS) in seven healthy human livers were determined and compared with those from patients with liver cirrhosis using the methods of enzymatic analysis, electrophoresis and CPC-cellulose microcolumn. The enzymatic analysis revealed that the major constituent of AMPS in the healthy human liver was heparan sulfate, with approximately equal lesser quantities of dermatan sulfate and hyaluronic acid, and small amount of chondroitin sulfates. These components were increased, especially dermatan sulfate and chondroitin sulfates, in the cirrhotic liver. The electrophoretic findings coincised with the results obtained by the enzymatic method.